Service Quality of Selected Resorts in the Central Philippines - Genove, Vito Carlo M.; Tayco, Ryan (Institut Pariwisata dan Bisnis Internasional, 2023)
The state of the hotels, resorts, and restaurant industry is dependent upon the quality of service exhibited by its frontliners and personnel. This study is to measure the service quality of selected resorts in the Municipality of Dauin, province of Negros Oriental, Philippines using a descriptive-correlational design. 120 customers of the six selected resorts that served as the respondents of this research. This study aims to measure the levels of customer satisfaction using the five dimensions of service quality: tangibility, reliability, responsiveness, assurance, and empathy. Data were collected mainly from the six selected resorts, after which results were tabulated, presented, analyzed, and interpreted. The findings show that tangibility is the weakest dimension while assurance is the strongest dimension of service quality. This implies that the level of satisfaction in all dimensions is yielding a positive SERVQUAL response. Hence, customers were satisfied with all dimensions of service quality.